Congenital nevus before and after onset of halo. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2011)
A 1-year-old boy, born full term normal delivery, was first observed due to a small nevus present since birth on his left knee. Physical examination (Fig. 1) showed a melanocytic nevu, about 1 cm in size, deeply pigmented with slightly irregular outline. Dermoscopy (Fig. 2) showed a globular pattern with brown and some bluish globules. After five years we reviewed the child before the summer for the appearance of a vitiligo halo around the nevus (Fig. 3). His mother reported to be affected by autoimmune thyroiditis. At the end of summer (Fig. 4) the halo expanded and took a sharp outline. Dermoscopy (Fig. 5, 6) showed on the center (C, residual nevus Fig. 6) irregular globules in regression without overt signs of inflammation, in the context of the halo (A in Fig. 5) blackish points and filaments up to the limit with the healthy skin (S Fig. 5).